2023
DOI: 10.3390/ijms24021256
|View full text |Cite
|
Sign up to set email alerts
|

Unscrambling the Role of Redox-Active Biometals in Dopaminergic Neuronal Death and Promising Metal Chelation-Based Therapy for Parkinson’s Disease

Abstract: Biometals are all metal ions that are essential for all living organisms. About 40% of all enzymes with known structures require biometals to function correctly. The main target of damage by biometals is the central nervous system (CNS). Biometal dysregulation (metal deficiency or overload) is related to pathological processes. Chronic occupational and environmental exposure to biometals, including iron and copper, is related to an increased risk of developing Parkinson’s disease (PD). Indeed, biometals have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 143 publications
(155 reference statements)
0
3
0
Order By: Relevance
“…Since Fe accumulation in the brain has been linked to PD, metal chelation could be a promising therapeutic approach [ 53 ]. Indeed, experimental studies using parkinsonian models have shown that Fe chelation reduces pathological α-synuclein accumulation [ 54 ] and oxidative stress [ 55 , 56 ].…”
Section: Protective Functions Of Mts Against Etiopathogenesis In Pdmentioning
confidence: 99%
“…Since Fe accumulation in the brain has been linked to PD, metal chelation could be a promising therapeutic approach [ 53 ]. Indeed, experimental studies using parkinsonian models have shown that Fe chelation reduces pathological α-synuclein accumulation [ 54 ] and oxidative stress [ 55 , 56 ].…”
Section: Protective Functions Of Mts Against Etiopathogenesis In Pdmentioning
confidence: 99%
“…[1] The concentration level of H 2 O 2 serves as a vital biological parameter for monitoring the physiological balance of living cells, and the deviations of the concentration levels can result in cellular dysfunction, cellular variability and apoptosis, potentially leading to serious health conditions including myocardial infarction, Parkinson's disease, and various cancers. [2,3] The development of efficient and reliable modus for the sensitive and selective detection of H 2 O 2 under physiological conditions is of paramount importance. In the past two decades, a variety of methods have been utilized to H 2 O 2 detection, including colorimetry, [4] spectrometry, [5] chemiluminescence, [6] positron emission tomography, [7] electrochemical methods, [8] and more comparison of the analytical performance of other assay methods on H 2 O 2 detection have been exhibited in Table S-1.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen peroxide (H 2 O 2 ) is a crucial small molecule mediator widely involved in cell growth and signal transduction [1] . The concentration level of H 2 O 2 serves as a vital biological parameter for monitoring the physiological balance of living cells, and the deviations of the concentration levels can result in cellular dysfunction, cellular variability and apoptosis, potentially leading to serious health conditions including myocardial infarction, Parkinson's disease, and various cancers [2,3] . The development of efficient and reliable modus for the sensitive and selective detection of H 2 O 2 under physiological conditions is of paramount importance.…”
Section: Introductionmentioning
confidence: 99%